Enabling xylose utilization in Yarrowia lipolytica for lipid production. Issue 9 (14th July 2016) - Li, Haibo; Alper, Hal S.
Abstract: The conversion of lignocellulosic sugars, in particular xylose, is important for sustainable fuels and chemicals production. While the oleaginous yeast Yarrowia lipolytica is a strong candidate for lipid production, it is currently unable to effectively utilize xylose. By introducing a heterologous oxidoreductase pathway and enabling starvation adaptation, we obtained a Y. lipolytica strain, E26 XUS, that can use xylose as a sole carbon source and produce over 15 g/L of lipid in bioreactor fermentations (29.3% of theoretical yield) with a maximal lipid productivity of 0.19 g/L/h. Genomic sequencing and genetic analysis pointed toward increases in genomic copy number of the pathway and resulting elevated expression levels as the causative mutations underlying this improved phenotype. More broadly, many regions of the genome were duplicated during starvation of Yarrowia . This strain can form the basis for further engineering to enhance xylose catabolic rates and conversion. Finally, this study also reveals the flexibility and dynamic nature of the Y. lipolytica genome, and the means at which starvation can be used to induce genomic duplications. Abstract : Yarrowia lipolytica is a non‐conventional yeast that can produce lipid for biofuel production effectively; but xylose, the second abundant sugar in biomass cannot be utilized efficiently by Y. lipolytica . By introducing a heterologous xylose pathway in Y. lipolytica followed by activation/adaptation through starvation, Y. lipolytica is enabled to utilize xylose as a carbon source for producing lipid.